The effect of soaking sago starch in acetate acids on the whiteness degree of sago flour. Issue 3 (July 2021) - Yumeina, Diyah; Adil, Suci; Samsuar,
Abstract: Sago flour soaking is one way to improve the white of sago that tends to turn brown and reddish because of the phenolase enzyme activity in sago. Some studies suggest that acetic acid can impede the encephalic tanning reaction that occurs in sago. This study aims to identify the characteristics of sago flour obtained from sago starch soaking in acetate solutions and to get the best of the sago flour. The method of this study uses Completely Randomized Design (CRD) with two factors, namely variations of submersion time (2 hours, 4 hours, 6 hours) and the acetic acid (CH3 COOH) concentration (0%, 0, 1%, 0, 25%). The data obtained were analyzed using Analysis of Variance (ANOVA) and followed by Duncan Multiple Range Test (DMRT) at a 5% significance level. Sago flour soaking with acetic acid has a significant effect on the quality of sago flour, such as the degree of whiteness, water content, and acidic level. The longer it takes to submerge and the higher the concentration of acetic acid, the degree of white, water content, and degree of acid sago flour also increases. All the results of this research qualified the quality requirements of sago flour according to the quality standard of sago flour.